Responsibility Of The Notary Department As A Consequence Of Secret Of The Minutes Deed Misuse By Its Employees - David Ayank Kurniawan; Siska Septiyanti; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
The purpose of this study is to identify and analyze: 1) The importance of the notary's obligation to safeguard the confidentiality of the contents of any particular act as referred to in Article 16 paragraph 1 of the letter (f) of Act No. 2 of 2014 Regarding Change of Law of 30 of 2004 About the Notary Department. 2). It is the responsibility of the Notary department for the abuse of confidentiality by millions of employees.This study is a type of normative juridical research, using a legislative and conceptual approach to Data collection derived from primary and secondary data, using interview methods and library studies. Data analysis techniques using qualitative data analysis.The result of the research is 1).The importance of the Notary's obligation to safeguard the confidentiality of the contents of the deed, particularly in the matter of Article 16 paragraph 1 letter (f) of Act No. 2 of 2014 About the Amendment of Act No. 30 of 2004 About the Notary Department is to keep everything confidential. and any evidence obtained for the making of the deed in accordance with the oath / appointment of the department. 2). The responsibility of the notary office is due to the misuse of confidentiality by the employees although in this case the notary does not commit a direct offense, because in one of the principles of civil liability there is a principle of absolute responsibility, whereby the person commits an error indirectly (due to negligence or negligence) heart) can be held responsible for the loss suffered by someone.Keywords: Notaries; Responsibilities; Minutes Deed.